Accountability and Management Transparency Masjid Finance Based on Principles Aman and Fathanah (Phenomenology Study in Mosques in Nganjuk Hamlet , Sugihwaras Village, Wonomulyo District, Polewali Mandar Regency, West Sulawesi Province) - Saiful Muchlis; Anna Sutrisna Sukirman; Ridwan Ridwan (The Indonesian Journal of Accounting Research, 2019)
This research is based on the antipasti community to the mosque management who usually do not understand financial management and are less transparent. This study aims to determine the application of accountability and transparency of mosque financial management based on the principles of trust and fathanah at Istiqomah Sugihwaras mosque. This research is a type of qualitative research. This study uses the Phenomenology approach where this research is carried out by explaining the existing phenomena by developing concepts and gathering facts through data as a means of supporting and seeing and relating to the reality that is in its implementation.The results of this study indicate that, Accountability and financial transparency of the Istiqomah Sugihwaras Mosque is in good condition, and is accountable to fellow administrators, mosque worshipers and to Allah. Judging from the Friday share report, Friday's Charity Box report, and monthly donors have been arranged as well as possible and announced every Friday. Istiqomah Mosque does not apply the principle of fathanah as seen from the ordinary court structure and dual positions in the mosque management so that the financial management of the mosque is not good. Transparency of the Istiqomah Mosque only relies on announcements every Friday before Friday prayers. So it is very necessary for training or guidance in financial management, especially non-profit financial institutions and is very much needed with the use of media such as notice boards as a means to communicate the results of the performance of takmir mosques.